"I Disrespectfully Agree": The Differential Effects of Partisan Sorting on Social and Issue Polarization. Issue 1 (25th March 2014) - Mason, Lilliana
<x xml:space="preserve">Abstract</x> Disagreements over whether polarization exists in the mass public have confounded two separate types of polarization. When social polarization is separated from issue position polarization, both sides of the polarization debate can be simultaneously correct. Social polarization, characterized by increased levels of partisan bias, activism, and anger, is increasing, driven by partisan identity and political identity alignment, and does not require the same magnitude of issue position polarization. The partisan‐ideological sorting that has occurred in recent decades has caused the nation as a whole to hold more aligned political identities, which has strengthened partisan identity and the activism, bias, and anger that result from strong identities, even though issue positions have not undergone the same degree of polarization. The result is a nation that agrees on many things but is bitterly divided nonetheless. An examination of ANES data finds strong support for these hypotheses.